Amending of fluorescence sensor signal localization in human skin by matching of the reflective index. - Churmakov, D. Y.; Meglinski, Igor V.; Greenhalgh, Douglas A. (Society of Photo-Optical Instrumentation Engineers (SPIE), 2004)
Fluorescence diagnostic techniques are notable amongst many other optical methods because they offer high sensitivity and non-invasive measurement of tissue properties. However, a combination of multiple scattering and physical heterogeneity of biological tissue hampers interpretation of the fluorescence measurements. Analyses of the spatial distribution of endogenous and exogenous fluorophores excitation within tissues and their contribution to the detected signal localization are essential for many applications. We have developed a novel Monte Carlo technique that gives a graphical perception of how the excitation and fluorescence detected signal are localized in tissues. Our model takes into account the spatial distribution of fluorophores, the variation of concentrations and quantum yield. We demonstrate that matching the refractive indices of the ambient medium and topical skin layer improves spatial localization of the detected fluorescence signal within the tissues.
Keywords: refractive index matching; fluorescence localization; Monte Carlo simulation; sampling volume; skin tissues; tattoo